Inclusion Policy in East Javanese Cultural Perspective and Its Implication on Guidance and Counseling - Asep Sunandar; Ediyanto Ediyanto; Fina Riswari; Fiolina Hana Puspitasari; Neny Yuniarti; Silvana Rahma Iswahyudi (Universitas Ahmad Dahlan, 2021)
The urgency of inclusive policies in a very diverse cross-cultural perspective is a form of follow-up to the implementation of inclusive education that provides equal and equal educational services to all children with diverse cultural backgrounds. The purpose of the inclusion policy study in the cultural perspective of East Java is to find out how the implementation of inclusion policies can represent the cultural diversity that exists in East Java. The implementation of inclusion policies is not only for disabilities, but also the implementation of inclusion policies is able to reach into various aspects of life that are developing in the people of East Java. This literature review aims to summarize how the concept of inclusion policy is in the perspective of East Java culture. The selection of articles started from peer-reviewed research journals at Google Scholar and Z-library. From this search, 14,700 articles were found. Then after screening the articles published from 2010 to 2020 and found 1045 articles. There were 10 articles that were studied and analyzed according to the topic discussed. The analysis technique used is content analysis. Based on the results of the analysis, it can be seen that it is necessary to implement inclusive education policies to improve the quality of life for persons with disabilities and individuals. Through formal education in the cultural perspective in East Java, it is expected to be able to overcome the diversity of social and cultural dimensions. The existence of a policy on inclusive education can realize the implementation of public services in the field of education and other fields that respect diversity and is not discriminatory for all individual learners. The implication of the results of this study is guidance and counseling teachers are required to have competence in providing services for children with disabilities.